Structural Characterization and Chemical Classification of Some Bryophytes Found in Latvia. Issue 7 (12th July 2013) - Maksimova, Viktorija; Klavina, Laura; Bikovens, Oskars; Zicmanis, Andris; Purmalis, Oskars
Abstract Bryophytes are the second largest taxonomic group in the plant kingdom; yet, studies conducted to better understand their chemical composition are rare. The aim of this study was to characterize the chemical composition of bryophytes common in Northern Europe by using elemental, spectral, and non‐destructive analytical methods, such as Fourier transform IR spectrometry (FT‐IR), solid‐phase 13C‐NMR spectrometry, and pyrolysis‐gas chromatography/mass spectrometry (Py‐GC/MS), for the purpose of investigating their chemotaxonomic relationships on the basis of chemical‐composition data. The results of all these analyses showed that bryophytes consist mainly of carbohydrates. Judging by FT‐IR spectra, the OH groups in combination of CO groups were the most abundant groups. The 13C‐NMR spectra provided information on the presence of such compounds as phenolics and lipids. It was found that the amount of phenolic compounds in bryophytes is relatively small. This finding definitely confirmed the absence of lignin in the studied bryophytes. Cluster analysis was used to better understand differences in the chemical composition of bryophyte samples and to evaluate possible usage of these methods in the chemotaxonomy of bryophytes.